Perceptions of prim gravidas on danger signs in pregnancy and childbirth at Bwaila hospital. - Phiri, Dunia Amran (Kamuzu University of Health Sciences, 2022)
Maternal mortality and morbidity rates remain a serious health, social and economic problem in developing countries. (PitroffR & Campbell O, 2000). In Malawi the maternal mortality rate is 984 per 100,000 live births (MDHS 2004) despite the safe motherhood initiatives. The purpose was to establish the perceptions of prim gravidas on danger signs in pregnancy and childbirth through a qualitative study hence find means of improve their health seeking behaviours and help reduce the maternal mortality and morbidity rates. The subjects of the study involved 15 prim gravidas aged 15-35 at antenatal clinic Bwaila hospital Data was collected using a semi structured interview guide and was analysed 1 manually using content analysis. Results indicated lack of knowledge in danger signs and most women perceived themselves as not being at risk while a few had misconceptions which made them perceive themselves as not be at risk. In conclusion: most people are not aware of the danger signs so, there is need for strategies to help empower women on knowledge for them to improve health seeking behaviours and reduce maternal mortality rates.